NCAA Exit Interviews and Surveys: Academic Experiences of College Athletes - Molly Harry (University of Kansas Libraries, 2021)
Institutions are required to conduct exit interviews and surveys (EIS) with departing athletes, however, these instruments are currently an untapped data source for further understanding the college athlete experience. This study examined 17 FBS institutions' exit interviews and surveys with 528 athletes, focusing on athletes' academic experiences. Analyses revealed that EIS questions pertaining to educational experiences focused on the following areas: academic services, overall academic experiences, time demands, coach support of academics, and faculty support. Athletes in this sample expressed overall positive academic experiences and gratitude for the academic services provided. Additionally, the majority of athletes noted few issues with time demands, strong coach support for their academic progress, and positive faculty interactions. These findings challenge some of the current literature noting negative educational experiences and opportunities for college athletes. Implications and recommendations for the field are discussed.